(untitled) (Research, Society and Development, 2022)
Since the discovery of Amyotrophic Lateral Sclerosis (ALS) there has been a wide search in the world for genetic and environmental elements that may cause it. With the majority of sporadic cases, it draws attention to possible environmental causes for the development and progression of the disease. Several studies on the epidemiological profile and potential risk factors for this disease were carried out in different regions of the world, but there are few data in Latin America and the Amazon, and in view of this need for investigation, this study was developed. To this end, a sample of 31 patients and 29 controls who attended consultations at the Outpatient Clinic of the Neurology Service of Hospital Ophir Pinto de Loyola (HOL) was obtained, and data were collected through questionnaires and notes in medical records. Subsequently, the epidemiological profile of these patients was evaluated, comparing risk factors between patients and controls. As a result, it was found that the patients have a profile similar to the literature, but with a longer average time to diagnosis and an age range of earlier onset of symptoms than usual. There was no statistical significance for exposure to risk factors between cases and controls. It is suggested the need for future prospective studies directed to each risk factor.